IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURAL PARAGRAPH THROUGH DEMONSTRATION METHOD - Linda Komariah (Universitas Negeri Medan, 2014)
This study concerns with improving grade VIII students’ achievement in writing procedural Paragraph through demonstration method. This research was conducted by using classroom action research. The subject of the study was grade VIII students of SMP N 2 Babalan which consisted of 35 students. The instruments for collecting data were primary data (writing test) and secondary data (interview sheet, observation sheet and questionnaire sheet). Based on writing scores, students’ score kept improving in every evaluation. In the test I the mean was 64,91, in the test II the mean was 74,57 . Based on interview, observation, and questionnaire sheet, it was found that teaching-learning process ran well. Students were active, creative to give their idea, enthusiastic, and interested in writing. The finding of the research showed that applying demonstration method significantly improved students’ writing achievement. Keyword: writing achievement, demonstration method, classroom action research.